2014
DOI: 10.1002/asia.201402224
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Spherical Li4Ti5O12 as High‐Performance Anodes for Lithium‐Ion Batteries

Abstract: Porous microspherical Li4Ti5O12 aggregates (LTO-PSA) can be successfully prepared by using porous spherical TiO2 as a titanium source and lithium acetate as a lithium source followed by calcinations. The synthesized LTO-PSA possess outstanding morphology, with nanosized, porous, and spherical distributions, that allow good electrochemical performances, including high reversible capacity, good cycling stability, and impressive rate capacity, to be achieved. The specific capacity of the LTO-PSA at 30 C is as hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…7,15 Moreover, the slopes in low frequency are directly proportional to the lithium ion diffusion coefficient (D Li ). [42][43][44] The D Li can be calculated from the plots in low frequency region according to the following equations: 42,45,46…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,15 Moreover, the slopes in low frequency are directly proportional to the lithium ion diffusion coefficient (D Li ). [42][43][44] The D Li can be calculated from the plots in low frequency region according to the following equations: 42,45,46…”
Section: Resultsmentioning
confidence: 99%
“…. Moreover, the slopes in low frequency are directly proportional to the lithium ion diffusion coefficient (D Li ) [42][43][44]. It is found that the sizes of semicircles forLi 4 Ti 5 O 12 /C and Li 4 Ti 5 O 12 /TiO 2 /C composites are smaller than that of pure Li 4 Ti 5 O 12 and Li 4 Ti 5 O 12 /TiO 2 composite.…”
mentioning
confidence: 99%
“…According to the equivalent circuit, R s represents the electrolyte resistancea nd R ct represents the charge-transfer resistance, [27] and the two indices were calculated by the equivalentc ircuit and are shown in Table 1. Whether using pure TiO 2 or TiO 2 -RGO electrodes, the impedance of electrodes decreases after cycling because of the solid-electrolytei nterphase (SEI)f ormation and electrode/electrolyte activation.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the discharge capacity of the pure LTO nanosheet drops rapidly to 83.1 mA h g À1 after 1000 discharge/charge cycles at the same rate, and the corresponding capacity retention is only 69.3%. The current research was also compared with other LTO-based, high rate electrodes in previous studies, including LTO-anatase TiO 2 composites, 11,13,[21][22][23][24] surface modified LTO, [35][36][37] nanostructured LTO, [38][39][40][41] and ion-doped LTO, 42,43 and these results are shown in Table 1. By comparison, the high rate cycling performance of the LTO-RTO electrode is comparable to that of the La-doped LTO and remarkably better than those of other LTO-based electrodes.…”
Section: Electrochemical Characterizationmentioning
confidence: 98%
“…44 It is thought that the nebulous substance covering the cycled LTO nanosheets is the product of side reactions with the electrolyte. So, it can be inferred that the in situ generated nanosized 34 154 after 100 cycles at 5 C 91 LiCrTiO 4 /MWCNT 35 115 after 200 cycles at 10 C 96 Carbon coated LTO 36 104 after 500 cycles at 10 C 90 Mesoporous LTO 37 120 after 300 cycles at 5 C 88 LTO nanoclusters 38 122 after 100 cycles at 5 C 88 Mesoporous LTO 39 144 after 200 cycles at 10 C 91 Core-shell LTO 40 131 after 1000 cycles at 10 C 95 Cu 2+ doped LTO 41 112 after 100 cycles at 10 C 98 La-doped LTO 42 140 after 1000 cycles at RTO sheets in the LTO-RTO electrode may play an important role in inhibiting the occurrence of side reactions during long-term electrochemical charge/discharge cycling. However, the mechanism is still unclear, and more work needs to be carried out.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%